Pengaruh Kecanduan Gadget Terhadap Interaksi Sosial Remaja di SMA - Anindhita Felisia Anggraheni; Dini Rakhmawati; Venty Venty (Scidacplus, 2026)
Gadget addiction among adolescents resulting from excessive use can reduce environmental awareness and impact social interaction. This study aims to analyze the effect of gadget addiction on the social interaction of students at Mranggen 1 Public High School using a quantitative ex-post facto method. Data were collected from 177 respondents using a gadget addiction questionnaire based on the theory of Kwon et al. (2013) and a social interaction questionnaire based on the theory of Sarwono (2010), and were analyzed using simple linear regression. The results showed a correlation coefficient of 0.422 and an R² value of 0.178, indicating that gadget addiction accounts for 17.8% of the variation in social interaction. A calculated F-value of 37.026 with a p-value of 0.000 indicates a significant effect. The regression equation Y = 127.986 − 0.508X indicates that an increase in gadget addiction reduces social interaction by 0.508 points per 1-unit increase.